Reliability and validity of the Istanbul Low Back Pain Disability Index in lumbosacral radiculopathy - (:unkn) unknown (IOS PRESS, 2021)
BACKGROUND: Lumbosacral radiculopathy is associated with a broad range of complaints; therefore, specific disability measurements should be validated for this condition. OBJECTIVES: The aim of this study was to investigate the validity and reliability of the Istanbul Low Back Pain Disability Index (ILBPDI) in lumbosacral radiculopathy. METHODS: Patients diagnosed with radiculopathy caused by a disc herniation were included. Disability and quality of life were evaluated with the Oswestry Disability Index (ODI) and Short Form-36 (SF-36), respectively. The severity of low back pain and leg pain were evaluated using a Numeric Rating Scale (NRS). The reliability of the ILBPDI was assessed using the Cronbach's alpha coefficient. The relation of ILBPDI with SF-36, ODI, NRS-back and NRS-leg scores were analyzed for convergent validity. The relation of the ILBPDI with age, body mass index (BMI), and disease duration was analyzed for divergent validity. Factor analysis was used to establish the internal construct validity. RESULTS: One hundred patients (55% female) were included in this study. The Cronbach's alpha coefficient was 0.92. The ILBPDI was found to be correlated with the ODI (rho: 0.619, p < 0.005) and NRS-leg score (rho: 0.597, p < 0.005), but not with NRS-back score (rho: 0.164, p > 0.05). The ILBPDI was significantly correlated with physical functioning (rho: 0.638, p < 0.005), bodily pain (rho: 0.488, p < 0.005), general health (rho: 0.264, p = 0.008) and social function (rho: 0.372, p < 0.005) subscales of SF-36 (convergent validity). The ILBPDI was not correlated with age, BMI, or disease duration (divergent validity). Factor analysis showed that the scale had three-factors which were correlated to bending forward, standing, and sitting activities. CONCLUSION: The ILBPDI is a valid and reliable instrument in patients with lumbosacral radiculopathy.
Keywords: Reliability and validity; low back pain; radiculopathy; disability evaluation; quality of life; LUMBAR DISC HERNIATION; QUALITY-OF-LIFE; VALIDATION; QUESTIONNAIRE; DIAGNOSIS; SEVERITY; SCIATICA; OUTCOMES; VERSION; SCALE